The "Joint Line Height Ratio" Assessing the Ankle Joint Line Level Before and After Total Ankle Replacement. Issue 4 (16th October 2019) - Harnroongroj, Thos; Hummel, Amelia; Sofka, Carolyn; Ellis, Scott J.; Deland, Jonathan; Demetracopoulos, Constantine
Category: Ankle Arthritis Introduction/Purpose: n important principle of joint replacement is to restore the joint line to its native level. Previous studies have demonstrated a correlation between clinical outcomes and our ability to restore the joint in total knee arthroplasty. To date, there has been no study to assess restoration of joint height in total ankle replacement (TAR). In addition, there is no accepted method for assess joint line height in patients who undergo TAR. The objective of this study is to develop a reliable radiographic ankle joint line level measurement. Additionally, the measure will be used to evaluate and compare ankle joint line levels seen on pre-TAR, post-TAR, and non-arthritic contralateral ankle radiographs. Methods: One hundred and twelve primary TAR patients with weightbearing preoperative (pre-TAR) and 1-year postoperative (post-TAR) anteroposterior (AP) ankle radiographs were retrospectively reviewed. Patients with bilateral disease, concomitant malleolar osteotomy, and component subsidence were excluded. Two raters measured the vertical intermalleolar distance (VIMD, Figure 1) and the vertical joint line distance (VJLD, Figure 1) for all radiographs (pre-TAR, post-TAR, and contralateral normal ankle) on two separate occasions. The measurement "joint line height ratio" was calculated as the ratio of the VJLD to the VIMD (Figure 1). Reliability was assessed using intraclass correlation coefficients (ICCs). Pearson correlation test was used to assess the level of correlation between the VJLD and the VIMD. The comparisons of pre-TAR, non-arthritic contralateral ankle, and post- TAR "joint line height ratio" were performed using paired t-tests and considered significantly different if p < 0.05. Results: Inter/intra-rater reliabilities of all measurements were excellent (r>0.9). Pearson correlation test demonstrated strong positive correlations of VIMD and VJLD with r 0.809 for pre-TAR and r 0.756 for post-TAR, p<0.001. Mean(SD) VIMDs for pre- TAR, non-arthritis contralateral ankle, and post-TAR were 17.91(4.79), 18.96(4.67) and 17.37(4.76) mm. Mean(SD) VJLDs for pre- TAR, non-arthritis contralateral ankle, and post-TAR were 26.49(4.64), 25.47(4.12) and 26.70(5.31) mm. Additionally, mean(SD) "joint line height ratio" for pre-TAR, non-arthritic contralateral, and post-TAR ankle radiographs were 1.54(0.31), 1.39(0.26) and 1.62(0.49). The "joint line height ratio" of pre- and post-TAR was significantly higher compared to non-arthritic contralateral ankle (p 0.0001 and < 0.0001), respectively. No significant difference in "joint line height ratio" was found between pre- and post-TAR(p = 0.15). Conclusion: The "joint line height ratio" was a reliable tool for assessing the ankle joint line pre and post-TAR. End-stage ankle arthritis leads to an elevated joint line compared to non-arthritic ankle. The joint line level after TAR was preserved to that measured before TAR, but not restored compared to the non-arthritic contralateral ankle. When performing TAR, joint line level restoration should be evaluated compared to the contralateral non-arthritic ankle radiograph. The amount of tibial cut should be minimized as much as possible to prevent further bone loss and ankle joint line elevation.